The effect of freeze-dried strawberry (Fragaria anannassa) powder on reproductive parameters of diet-induced obese male rats / Nur Rohmah Suwandi - Suwandi, Nur Rohmah (2019)
Obesity alters physical being and causes hormonal imbalance, metabolic abnormalities and oxidative stress. Obesity has also been implicated in reduced reproductive functions in male by compromising on sperm parameters and reducing levels of androgenic hormones. Attenuating the harmful effects of metabolic abnormalities and oxidative stress with agents containing both antioxidant and anti-obesity properties such as strawberry may be beneficial therapeutically and offer safe options to health and reproductive performance